Overview of Performance of Selected Low-Cost Atmospheric Sensor Nodes in Ghanaian urban areas. - Gameli Hodoli, Collins; Coulon, Frederic; Mead, Iq (Cranfield University, 2020)
The attached dataset is specific to the overview of performance of selected low-cost atmospheric sensor nodes in Ghanaian urban areas.
Keywords: Low-Cost Sensors'; 'air pollution exposure'; 'Air quality monitoring'; 'Atmospheric Sciences'